Status Kesuburan Tanah Inceptisol pada Penggunaan Lahan Kelapa Sawit di Desa Pengadang Kecamatan Sekayam Kabupaten Sanggau - Emi, Suhemi (Jurnal Pedontropika : Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2022)
ABSTRACTSeveral constraints on the chemical properties of inceptisol soils, including acid soil reactions, soil organic matter generally varies, as well as the value of cation exchange capacity, bases can be exchanged, base saturation, nutrient reserves and nutrient status of P and K are low, but have saturation (Al) tall one. The purpose of the study was to analyze the nutrient status and soil fertility of Inceptisols on oil palm land use in Pengadang Village, District, Sekayam, Sanggau Regency and suggestions for fertilization to support maximum oil palm production. Soil sampling was carried out on 5-year-old oil palm plantations. Diagonal soil sampling method with three replications. Analysis of chemical properties consisting of pH, C-organic, N-total, P-total, P-available, K-total, K-dd, CEC, KB, and soil Al were carried out in the soil chemistry and fertility laboratory. The results of the average nutrient status on oil palm land are N-total nutrient status of 0.20% (low), available P of 15.09 ppm (low), CEC of 9.06 cmol (+) kg-1 (low ), C-organic by 1.42% (low). P-total status is 37.5 ppm (very low), K-total is 87.5 ppm (very low), K-available is 32.5 ppm (very low), KB is 19.30% (very low) , Al saturation is 39.55% (high) and the soil fertility status of oil palm land is classified as very low. Suggestions for single fertilization of urea is 255.56 kg/ha, TSP is 142.81 kg/ha and KCL is 509.13 kg/ha and Phonska 15:15:15 NPK compound fertilizer is 428.40 kg/ha, and urea is 85 ,84 kg/ha and KCL 402,01 kg/ha, to increase the lack of nitrogen and potassium elements in the soil. The need for dolomite lime is 2,400 kg/ha.